L'image de marque des villes wallonnes - Loïc Scatton; Serge Schmitz (Belgeo)
City branding practices have become widespread but few studies measure their effects on medium-sized cities. Through an analysis of the practices of city branding and internal and external images of the cities of Liege and Charleroi, this article points out the relative strengths and weaknesses of the images of each of the Walloon cities, among their businessmen, vis-a vis those of the other Walloon city. The images of these two cities are composites and branding policies are still in their infancy. These policies have followed a top-down approach which may explain the limited use of the two brands even if they use ideas shared by local entrepreneurs. However the research underlines the absence of opinions on certain characteristics of the cities or a negative view which often requires works in the field but also better communication.